CLINICAL-DEMOGRAPHIC ASPECTS OF SCORPION STING IN AL SULAIMANEYAH PROVINCE: HOW FREQUENT IS HYPOCALCAEMIA IN THE VICTIMS? - Hiwa Omer Ahmed; Anwar Hama Ranj (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿Background: Injuries from scorpions and other insects usually causes local symptoms such as pain, redness, swelling and itching; most are non venomous or mildly venomous. The main effect of the sting comes from the venom, which is water soluble, antigenic, heterogeneous mixture of enzymes and substances. Systemic symptoms and signs of envenomation appear in 15 % of those who sustain scorpion stings, presented as diverse cardiovascular and neuromuscular features, while some patients may present with other features such as excessive salivation, dysphagia, and nausea and vomiting which may reflect hypocalcemia, causing autonomic storm and acetylcholine excess. There are a few papers in the literature about hypocalcaemia and it seems to have been underestimated and largely ignored as a presentation of scorpion sting; but it may be the cause of most neuromuscular features in scorpion victims.Aim: This work aimed to find the frequency of hypocalcaemia in victims of scorpion stings in the Al Sulaimaniyah province and to raise awareness of the problem in our practice, in order to manage the patients in time with better outcomes.Methods: All the victims of scorpion sting who arrived at the Casualty Hospital in Al Sulaimaniyah City during a 12-month period were considered; in addition, the retrospective period 1st March 2009 to 1st September 2009 and from 1st March 2010 to 1st September 2010 as the prospective periods of the work. Al Sulaimaniyah Teaching Hospital is a tertiary hospital in Al Sulaimaniyah City, Kurdistan, Iraq, which serves a population of 1.25 million people.Demographic data were recorded, including the histories of the stings and the physical findings of the victims. When hypocalcaemia was suspected Chvostek-Weiss and Trousseaus signs were elicited and blood from the patient was sent for investigation including serum calcium.Results: Most of the patients sustained the sting on an upper limb (170/318 = 53%) and most were stung once, although a small number had multiple sting marks. Although the sting of a scorpion is sharp and it is not easy, in the presence of local edema and sweating, to identify the number of stings, we noticed two sting marks (2/318 = 06%) and three sting marks (3/318 = 0.94%). More than half the stung patients came from a city (62%), most of them were stung between 6pm and 12 midnight (111/318 = 34.9%) or between 6am and 12 noon ( 79/318 = 24.8%). Most of them reached the Casualty Hospital within one hour of being stung (186/318 = 58.5%). All the victims were tested for serum calcium and serum electrolyte; while eighteen patients showed features of hypocalcaemia. In 13 of these (13/18 = 72.2%) this had turned to hypocalcaemia (less than 8.5 mg/dl), but none of them showed any other electrolyte abnormality. These 13 patients were sent for ECG, which in nine cases gave normal readings, but the rest (4) showed a shortened ST segment and two of them had ventricular ectopics.Conclusion: Hypocalcaemia is evident in scorpion victims; in our practice in casualty wards, we should be more suspicious of this possibility. We suggest a routine estimation of serum calcium in victims of scorpion stings.